The unique behaviour of Nasalis larvatus in Bako National Park - Mohamad, Kombi; Halik, Akop; Anuar, Japar; Mohd Tajuddin, Abdullah; Madinah, Adrus (Department of Wildlife and National Parks (PERHILITAN) Peninsular Malaysia, 2023)
One of the attractions for tourists to visit Bako National Park is the presence of Nasalis larvatus (Proboscis Monkey) in the National Park. Therefore, in this chapter the unique behavior of N. larvatus in Bako National Park has been studied and recorded and is likely to be different from elsewhere. There were seven categories of behaviors that were successfully recorded, comprising various activities and movement patterns which involved their feeding, resting, agonistic, grooming, solicitation, copulation and locomotion. The categories are then break down into several characteristic activities and actions, such as, jumping, leaping, quadrupedal walking, chasing, slapping, biting, facial threats, postural threats, grooming, solicitation, copulation and others miscellaneous behavior. The most frequently observed behaviors during the observations of this research were eating, traveling and resting. Reports on the behavioral data provided are important to help improve our understanding of the behavioral patterns of wild N. larvatus in Bako National Park.